Effects of a single dose of the acetylcholinesterase inhibitor velnacrine on recognition memory and regional cerebral blood flow in Alzheimer's disease. - Ebmeier, K; Hunter, R; Curran, S; Dougal, N; Murray, C; Wyper, D; Patterson, J; Hanson, M; Siegfried, K; Goodwin, G (1992)
The effects of a single oral dose of the acetylcholinesterase inhibitor velnacrine maleate on word and object recognition memory and regional uptake of 99mTc-exametazime were examined in patients with Alzheimer's disease. Word recognition memory was marginally improved 2 h after 75 mg velnacrine. With the same dose of velnacrine a relative increase in superior frontal uptake of 99mTc-exametazime was shown with single photon emission computed tomography (SPECT). This suggests increased regional perfusion and metabolism as a consequence of cholinergic stimulation. The effect did not co-vary with the degree of memory improvement, but, instead, more cognitively impaired patients showed a greater increase in tracer uptake after velnacrine, suggesting cholinergic hypersensitivity in the brains of Alzheimer patients.